257 The Effect of the COVID-19 Pandemic on Mental Health Associated Trauma, Admissions and Fractures at a London Major Trauma Centre. (12th October 2021) - Jamal, M S; Hay, D; Al-Tawil, K; Petohazi, A; Gulli, V; Bednarczuk, N; Baldwin-Smith, R; Gibbons, J; Sinha, J
Abstract: Aim: Non-injury related factors have been extensively studied in major trauma and shown to have a significant impact on patient outcomes, with mental illness and associated medication use proven to have a negative effect on bone health and fracture healing. We report the epidemiological effect of COVID-19 pandemic on mental health associated Orthopaedic trauma, fractures, and admissions to our centre. Method: We collated data retrospectively from the electronic records of Orthopaedic inpatients in an 8-week non-COVID and COVID period analysing demographic data, referral and admission numbers, orthopaedic injuries, surgery performed and patient co-morbidities including psychiatric history. Results: here were 824 Orthopaedic referrals and 358 admissions (6/day) in the non-COVID period with 38/358 (10.6%) admissions having a psychiatric diagnosis and 30/358 (8.4%) also having a fracture. This was compared to 473 referrals and 195 admissions (3/day) in the COVID period with 73/195 (37.4%) admissions having a documented psychiatric diagnosis and 47/195 (24.1%) a fracture. 22/38 (57.9%) and 52/73 (71.2%) patients were known to mental health services, respectively. Conclusions: Whilst total numbers utilising the Orthopaedic service decreased, the impact of the pandemic and lockdown disproportionately affected those with mental health problems, a group already at higher risk of poorer functional outcomes and non-union. The proportion of patients with both a fracture and a psychiatric diagnosis more than doubled and the number of patients presenting due to a traumatic suicide attempt almost tripled. It is imperative that adequate support is in place for vulnerable mental health patients, particularly as we are currently experiencing the "second wave" of COVID-19.